2015
DOI: 10.4161/15592324.2014.989752
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death in plants: A chloroplastic connection

Abstract: Programmed cell death (PCD) is an integral cellular program by which targeted cells culminate to demise under certain developmental and pathological conditions. It is essential for controlling cell number, removing unwanted diseased or damaged cells and maintaining the cellular homeostasis. The details of PCD process has been very well elucidated and characterized in animals but similar understanding of the process in plants has not been achieved rather the field is still in its infancy that sees some sporadic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…While the link between cell death regulation, oxidative stress, DIEL REDOX FLUCTUATIONS REGULATE DIATOM CELL FATE and the mitochondria was long established in mammalian, plant, and even diatom cells (Saraste and Pulkki 2000, Scott and Logan 2008, Graff van Creveld et al 2015, the chloroplast received less attention. Recent studies emphasize the chloroplast's contribution to PCD as a major ROS producer, especially during stress (Doyle et al 2010, Ambastha et al 2015, Van Aken and Van Breusegem 2015. Taken together, we suggest that the chloroplast GSH pool plays a significant role in mediating diatom's response to stress.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…While the link between cell death regulation, oxidative stress, DIEL REDOX FLUCTUATIONS REGULATE DIATOM CELL FATE and the mitochondria was long established in mammalian, plant, and even diatom cells (Saraste and Pulkki 2000, Scott and Logan 2008, Graff van Creveld et al 2015, the chloroplast received less attention. Recent studies emphasize the chloroplast's contribution to PCD as a major ROS producer, especially during stress (Doyle et al 2010, Ambastha et al 2015, Van Aken and Van Breusegem 2015. Taken together, we suggest that the chloroplast GSH pool plays a significant role in mediating diatom's response to stress.…”
Section: Discussionmentioning
confidence: 53%
“…, Ambastha et al. , Van Aken and Van Breusegem ). Taken together, we suggest that the chloroplast GSH pool plays a significant role in mediating diatom's response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an important role of chloroplasts in PCD in plant leaves has emerged (Ambastha et al, 2015). This process is mediated by the singlet oxygen ( 1 O 2 ) produced by the PSII and its lightharvesting antennae (Krieger-Liszkay et al, 2008;Shapiguzov et al, 2012), and is observed as microlesions in the green plant tissues.…”
Section: Modulation Of Activities Of Ion Channels and Transporters Bymentioning
confidence: 99%
“…Of all the LMMs identified, only four were reported to develop lesion mimics and an early senescence phenotype. The destruction of chloroplasts indicates that lmes2 may go though PCD (Ambastha et al, 2015). SPL28, which is located on the long arm of chromosome 1, encodes a clathrin-associated adaptor protein complex 1; this encoding accounts for the formation of lesion mimics and early senescence (Qiao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The content of chlorophyll a, chlorophyll b, and carotenoids in lesion mimic leaves decreased very significantly in comparison with those of the wild-type; this decrease correlated with the destruction of chloroplasts in lmes2. The destruction of chloroplasts indicates that lmes2 may go though PCD (Ambastha et al, 2015). In addition, a poor photosynthetic rate may account for abnormal characteristics in lmes2, for example, shorter plant stature, fewer tillerings, and poor grains.…”
Section: Discussionmentioning
confidence: 99%